Logan Medallist 1. Seeking the Suture: The Coast-Cascade Conundrum - Monger, Jim W.H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
The boundary between rocks assigned to the Intermontane superterrane in the interior of the Canadian Cordillera and those of the Insular superterrane in the westernmost Cordillera of British Columbia and southeastern Alaska lies within/along the Coast Mountains, in which is exposed the core of an orogen that emerged as a discrete tectonic entity between 105 and 45 million years ago. Evidence from the Coast Mountains and flanking areas indicates that parts of the Intermontane superterrane (in Stikinia and Yukon-Tanana terranes) were near those of the Insular superterrane (Wrangellia and Alexander terranes) by the Early Jurassic (~180 Ma). This timing, as well as paleobiogeographic and paleomagnetic considerations, appears to discount a recent hypothesis that proposes westward-dipping subduction beneath an intra-oceanic arc on Insular superterrane resulted in arc-continent collision and inaugurated Cordilleran orogenesis in the Late Jurassic (~146 Ma). The hypothesis also relates the subducted ocean that had separated the superterranes to a massive, faster-than-average-velocity seismic anomaly in the lower mantle below the eastern seaboard of North America. To create such an anomaly, subduction of the floor of a large ocean was needed. The only surface record of such an ocean in the interior of the Canadian Cordillera is the Cache Creek terrane, which lies within the Intermontane superterrane but is no younger than Middle Jurassic (~174 Ma). This terrane, together with the probably related Bridge River terrane in the southeastern Coast Mountains, which is as young as latest Middle Jurassic (164 Ma) and possibly as young as earliest Cretaceous (≥ 130 Ma), appear to be the only candidates in Canada for the possible surface record of the seismic anomaly.